Pengaruh Solvabilitas, Kecukupan Modal, Dan Likuiditas Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi - Rahmasari, Azra Meilana; Hidayat, Rendra Arief (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of solvency, capital adequacy, and liquidity on firm value with profitability as a moderating variable. This study uses quantitative methods and documentation techniques. Data processing is carried out using SPSS version 25, while data analysis techniques use multiple linear regression analysis and moderated regression analysis. The sample of this study is a company engaged in the financial sector, banking sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The results of the study indicate that solvency and capital adequacy have a positive effect on firm value, while liquidity has a negative effect on firm value. Profitability can moderate the relationship between solvency, capital adequacy, and liquidity on firm value.